The impact of dexmedetomidine vs midazolam on coagulation factors during nasal surgery - Karaaslan, Kazim; Gülcü, Nebahat; Yilmaz, Fahrettin; Serin, Erdinç; Çolak, Cemil; Koço?lu, Hasan (My University, 2008)
Objective: Dexmedetomidine is an ?2 adrenergic receptor agonist and has sedative analgesic properties. We aimed to investigate the effects of dexmedetomidine coagulation system in monitored anesthesia care (MAC) patients, and to compare it with that of midazolam. Material and Methods: Sixty patients undergoing nasal surgery with local anesthesia were recruited. In Group D, dexmedetomidine was infused iv 1 ?g kg-1 over 10 min followed by 0.5 ?g kg-1 h-1. In Group M, midazolam was given iv 40 ?g kg-1 followed by 50 ?g kg-1 h-1. The effects of both drugs on coagulation system were evaluated by means of hemoglobin (Hb), hematocrit (Hte), platelet count, fibrinogen, protrombin time, active partial tromboplastine time (aPTT), INR, protein C, protein S and antitromhin III (ATIII) parameters with preoperatively (t0), early (t1) and 6 hours after postoperatively (t2). Results: Postoperative early (t1) and late (t2) Hb, Hte, aPTT and ATIII were decreased in both groups, and fibrinogen were decreased on these times in group M compared with preoperative values (p<0.05). Fibrinogen values were lower in t1 and t2 measurement in group M compared with group D (p<0.05). Conclusion: We conclude that the uses of dexmedetomidine or midazolam in MAC for nasal surgery do not have any effect on coagulation parameters.
Nazal cerrahi olgularinda deksmedetomidin ve midazolam kullaniminin koagülasyon üzerine etkileri
Keywords: Coagulation; Dexmedetomidine; Midazolam